Study on the Influence of OVPD on Pipeline Interference - WANG Lei-lei, GE Cai-gang, MOU Xiao-liang, JIANG Ka-ke, LIU Guo, DU Yan-xia (Cailiao Baohu)
A buried steel pipeline paralleled with the subway line has been seriously interfered by the metro stray current.The rail ground potential protection device inside the subway station was frequently switched on.Through synchronous monitoring of the rail/soil potential data and the ON/OFF potential data of the pipeline and the comparative analysis, the interference degree and law of the pipeline by metro stray current under the closed and unclosed state of the over-voltage protection device(OVPD)were studied.Results showed that as the ground potential protection device switched on, the stray current was leaked and absorbed through the grounding grid of the subway station, and the amplitude of the ON/OFF potential fluctuation of the pipeline became large, increasing the interference degree and the length of unprotected pipeline, meanwhile, the pipeline sections close to the grounding grid of subway station and those away from the grounding grid of subway station corresponded to the flowing in or flowing out of the stray current, respectively.Analyses indicated that when the OVPD was switched on, the grounding grid of station became one of the main stray current leakage points of the subway system.In the studied case, the peak of interference occurred at the pipeline section near the subway station and the time of stray current flowing out of the pipeline was less than that of inflow.When the OVPD was switched off, the shift of the pipeline potential in most of the time was related to the rail/soil potential fluctuation, but in a small part of the time, the shift of the pipeline potential was not related to the rail/soil potential fluctuation, indicating that for the studied case, there was other stray current contributing to the interference suffered by pipeline besides the stray current flowing in and out of the measured rail pipeline.